Developing Edumatika.id: An Interactive Web-Based e-Worksheet to Enhance Elementary Students' Mathematics Learning Outcomes - Budi Setiawan; Lingga Nico Pradana; Hendra Erik Rudyanto (Universitas PGRI Madiun, 2025)
Despite the growing use of digital tools in elementary mathematics education, most existing electronic worksheets remain limited to static content and lack interactivity, immediate feedback, and support for independent home-based learning. This study aimed to develop and evaluate Edumatika.id, a web-based interactive mathematics e-Worksheet designed to enhance the mathematical competence of Grade II elementary school students. A Research and Development (R&D) approach was employed using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The product was validated by two material experts and two media experts, then tested through one-to-one evaluation (n = 3), small-group evaluation (n = 5), and a field trial (n = 11) involving Grade II elementary school students. During the field trial, students used the platform independently at home for one week under parental supervision. Expert validation showed high feasibility, with average scores of 83.50% (material experts) and 89.00% (media experts). Practicality testing yielded consistently favorable results: 87.88% (one-to-one), 78.86% (small-group), and 87.50% (field trial). Parents reported an overall positive perception of home implementation (78.45%), particularly regarding parental support (81.82%) and student motivation (80.00%), though independent learning (73.81%) scored comparatively lower. Students' mean mathematics achievement improved from 7.00 (pretest) to 8.18 (posttest), with 81.8% of students showing gains. Edumatika.id distinguishes itself from prior e-Worksheets by integrating interactive materials, three-dimensional visualizations, game-based exercises, immediate formative feedback, and cross-device accessibility within a single platform. These findings indicate that Edumatika.id is a valid, practical, and promising medium for supporting elementary mathematics learning both at school and at home.